Nilai Kearifan Lokal dalam Cerita Rakyat Jepang (Minwa) - Unsriana, Linda (Humaniora, 2013)
Generally, local wisdom can be understood as local ideas that are thoughtful, full of wisdom, good value, embedded and followed by members of the community. One of the oral cultural traditions such as folklore also contains local wisdom in the content of the story. Folk tales as part of folklore could be said keeping a number of cultural system information such as philosophy, values, norms, behavior. Folklore also implies local wisdom embodied behind the story. Local wisdom that exists in folklore relates to morals and ethical characters shown in the dialog. Morals and ethics are part of the manners. Japan also has a lot of interesting folklore, which have also been translated into many languages, including Urashima Taro, Tsuru no ongaeshi, Shita kiri suzume, Kintaro, Hanasaki Jiisan, and many more. At the conclusion, it is found the value of local wisdom of a nation, can be found in the national folklore. There are a lot of moral values in folklore, especially minwa, one them is the value to return the favor or ongaeshi.